2021
DOI: 10.1021/acsami.0c22808
|View full text |Cite
|
Sign up to set email alerts
|

Effective Dark Current Suppression for High-Detectivity Organic Near-Infrared Photodetectors Using a Non-Fullerene Acceptor

Abstract: Near-infrared organic photodetectors (NIR OPDs) have attracted considerable attention because of their inherent advantages such as a tailorable light absorption property, low-cost fabrication, compatibility with flexible substrates, and room-temperature operation. In particular, the development of NIR detection between 900 and 950 nm is crucial for noise-free communication in ambient environments. In this work, we demonstrate high-detectivity NIR OPDs at 900–950 nm by employing a non-fullerene acceptor (ITIC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…The surface roughness decreased with the temperature increasing, and the 100 °C-casted film exhibited a smooth and nanosized phase separation surface with the lowest roughness (2.11 nm), revealing an optimized interfacial contact and subdued carrier recombination. [19] The optimized morphology of the 100 °C-casted film demonstrated that TIAA strategy inhibits the formation of large scale PBDB-T aggregates and contributes to the formation of smaller-scale D/A phase separation structure and bicontinuous interpenetrating networks. [18d-e] Figure 2f-i and Figure S8 (Supporting Information) are the 2D Grazing-incidence wide-angle X-ray scattering (GIWAXS) data and corresponding line-cut profiles of these BHJ films, implemented to explore the molecular packing and crystallinity.…”
Section: R Abmentioning
confidence: 99%
“…The surface roughness decreased with the temperature increasing, and the 100 °C-casted film exhibited a smooth and nanosized phase separation surface with the lowest roughness (2.11 nm), revealing an optimized interfacial contact and subdued carrier recombination. [19] The optimized morphology of the 100 °C-casted film demonstrated that TIAA strategy inhibits the formation of large scale PBDB-T aggregates and contributes to the formation of smaller-scale D/A phase separation structure and bicontinuous interpenetrating networks. [18d-e] Figure 2f-i and Figure S8 (Supporting Information) are the 2D Grazing-incidence wide-angle X-ray scattering (GIWAXS) data and corresponding line-cut profiles of these BHJ films, implemented to explore the molecular packing and crystallinity.…”
Section: R Abmentioning
confidence: 99%
“…In particular, there is still an open question of whether a large phase separation in the active layer is beneficial for suppressing the dark current and thereby improving the detectivity. Excessively large phase separation with extremely pure domains was reported to result in poor interfacial contact, increased dark current, and increased photocarrier recombination. On the other hand, excessive small phase separation is reported to form impure domains with intricate charge-transporting pathways, causing a similar recombination issue as well . No matter which one describes the general behavior, the conclusion must be drawn by investigating the effect of the BHJ morphology on a controlled materials system and by employing relevant device physics to interpret the charge transport behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Along with unprecedented progress in OLEDs and OSCs, OPDs have also progressed rapidly. , In particular, cavity-enhanced organic photodiodes have realized narrowband photodetection in the whole range from ultraviolet (UV) to near-infrared (NIR), and high-performance broadband OPDs based on NFAs have been reported with ultralow noise and a fast response. Furthermore, OPDs with a photomultiplication effect have also been achieved by multiple groups. Phototransistors as another type of photodetector exhibit great potential for multipixel imaging and wearable electronics and can be easily integrated with the well-established readout circuits. However, recently developed organic phototransistors (OPTs) are mainly limited by the following factors.…”
Section: Introductionmentioning
confidence: 99%